2016
DOI: 10.1155/2016/1908164
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Effects of Hydrogen Peroxide on Human Lung Cancer Cells: Potential Therapeutic Implications

Abstract: Lung cancer has a very high mortality-to-incidence ratio, representing one of the main causes of cancer mortality worldwide. Therefore, new treatment strategies are urgently needed. Several diseases including lung cancer have been associated with the action of reactive oxygen species (ROS) from which hydrogen peroxide (H2O2) is one of the most studied. Despite the fact that H2O2 may have opposite effects on cell proliferation depending on the concentration and cell type, it triggers several antiproliferative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 122 publications
(132 reference statements)
4
53
0
1
Order By: Relevance
“…Hydrogen peroxide, a product of MnSOD, has also been shown to play important roles in controlling cancer cell proliferation, differentiation, and cell cycle . While the role of elevated hydrogen peroxide in cancer have yielded conflicting results, and there is a possibility that hydrogen peroxide is protective against cancer; our results provide direct evidence in support of the concept that high levels of MnSOD, and increased hydrogen peroxide serves as the tumor promoting mechanism of UCP2. It would be further interesting to study further if by specifically targeting MnSOD, treatments may develop to inhibit UCP2 overexpression in cancers and, thereby, diminish tumorigenesis.…”
Section: Discussionsupporting
confidence: 71%
“…Hydrogen peroxide, a product of MnSOD, has also been shown to play important roles in controlling cancer cell proliferation, differentiation, and cell cycle . While the role of elevated hydrogen peroxide in cancer have yielded conflicting results, and there is a possibility that hydrogen peroxide is protective against cancer; our results provide direct evidence in support of the concept that high levels of MnSOD, and increased hydrogen peroxide serves as the tumor promoting mechanism of UCP2. It would be further interesting to study further if by specifically targeting MnSOD, treatments may develop to inhibit UCP2 overexpression in cancers and, thereby, diminish tumorigenesis.…”
Section: Discussionsupporting
confidence: 71%
“…Even if ROS have a paradoxical effect on cancer cell proliferation (Vilema-Enríquez et al, 2016). Recently some publications have highlighted plasma-induced hydrogen peroxide induced by plasma as a new approach of cancer treatment (Boehm and Bourk, 2017;Judée et al, 2016;Kaushik et al, 2015).…”
Section: Hydrogen Peroxide (H 2 O 2 )mentioning
confidence: 99%
“…pathways via other mechanisms such as the nuclear factor-κB MAPK pathway (12,13). Furthermore, a previous study demonstrated that increased p38 activity produced a positive feedback to enhance ROS generation by upregulating nicotinamide adenine dinucleotide phosphate-oxidase, H 2 O 2 and p38 to develop a positive feedback loop (14).…”
Section: Hydrogen Peroxide Promotes the Expression Of Angiopoietin LImentioning
confidence: 99%